2000
DOI: 10.1093/fampra/17.6.455
|View full text |Cite
|
Sign up to set email alerts
|

Developing a 'consultation quality index' (CQI) for use in general practice

Abstract: We have outlined possible uses for the CQI as part of the packages assessing quality of care by doctors and practices. The measure may also have a part to play in recognizing poorly performing doctors. We suggest how CQI scores could contribute to an incentive scheme to reward good consulting practice. Further work is in hand to compare doctors' CQI scores with scores based on performance indicators constructed from routine NHS data on prescribing and preventive medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 11 publications
1
40
1
3
Order By: Relevance
“…On the other hand, where doctors had at least 25 'other language' enablement scores to compare with their 'English language' scores, the correlation was r = 0.72. 5 So, although we agree again with Mead et al that caution has to be applied before using enablement on its own as an element of the national quality programme, we do not see why it could not contribute to a new QOF 'interpersonal care' measure now. Indeed we have proposed one such measure in the BJGP -the CQI-2.…”
contrasting
confidence: 50%
“…On the other hand, where doctors had at least 25 'other language' enablement scores to compare with their 'English language' scores, the correlation was r = 0.72. 5 So, although we agree again with Mead et al that caution has to be applied before using enablement on its own as an element of the national quality programme, we do not see why it could not contribute to a new QOF 'interpersonal care' measure now. Indeed we have proposed one such measure in the BJGP -the CQI-2.…”
contrasting
confidence: 50%
“…[2][3][4][5][6][7][8] The items were designed to determine patients' feelings of confidence, ability, and coping following a consultation.…”
Section: Enablementmentioning
confidence: 99%
“…It has been suggested that quality can be assessed additionally by measuring consultation length, continuity of care, and patient enablement, reflecting the core values of primary care. 2 In this model, enablement is a measure of the outcome of consultations. This paper examines the enablement concept in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that in longer consultations doctors prescribe less [4,5], listen better to their patients, identify more problems, explore more psychosocial problems and provide more health promotion [3,6]. When we take these measures as a proxy for quality, longer consultations seem to be better [5,7,8]. Howie and coworkers [8,9] showed that two major characteristics of primary care, holism and patient centredness, are both promoted by longer consultations.…”
Section: Introductionmentioning
confidence: 99%
“…When we take these measures as a proxy for quality, longer consultations seem to be better [5,7,8]. Howie and coworkers [8,9] showed that two major characteristics of primary care, holism and patient centredness, are both promoted by longer consultations. Ridsdale et al [10] found in longer consultations doctors and patients to show significantly different behaviour.…”
Section: Introductionmentioning
confidence: 99%